Increased paediatric emergency mental health and suicidality presentations during COVID‐19 stay at home restrictions. (22nd November 2021) - Carison, Anna; Babl, Franz E; O'Donnell, Sinead M
Abstract: Objective: Anecdotal reports indicate an increase in mental health presentations and acuity to EDs during the COVID‐19 pandemic and associated stay at home restrictions. Paediatric and adolescent data to confirm this are unavailable in the Australian setting. Methods: Retrospective electronic medical record review of all ED patients with mental health discharge codes at a large tertiary children's hospital in Australia during the period of stay at home restrictions from 1 April to 30 September 2020 compared with the same dates in 2019. Results: We found a 40% decrease in ED presentations (18 935–11 235) with a concurrent 47% increase in mental health presentations (809–1190) to ED during the study periods between 2019 and 2020. This resulted in an increase of 100 mental health admissions from ED. Diagnoses with greatest percentage increases were eating disorders, social issues and suicidality. We found suicidality presentation numbers were highest in June to September 2020 compared with 2019. Patients with a diagnosis of suicidality had a higher rate of re‐presentation in 2020 (1.83 presentations per patient) compared to 2019 (1.38 presentations per patient). Conclusions: Despite an overall decrease in ED presentations, the absolute increase in mental health presentations for children and adolescents during the stay at home restriction period was pronounced. It is unclear how sustained this change and the impact on mental health resource use will be post‐pandemic. Abstract : We explored the impact of prolonged COVID‐19 restrictions in Melbourne, Australia on mental health and specifically suicidality presentations to the paediatric ED. We found a 47% increase in all mental health presentations and a 59% increase in suicidality presentations during the stay at home restriction period in 2020, compared with the same dates in 2019.